Evaluation of masticatory performance and level of satisfaction of users of removable partial dentures: emphasis on the importance of RPDs in the age of implantology (Research, Society and Development, 2022)
Objective: To evaluate the masticatory performance and the level and satisfaction of partially edentulous individuals, after being rehabilitated with removable partial dentures (RPDs), emphasizing the importance of this treatment for oral health in the context of current dentistry where osseointegrated dental implants have been widely used. Methods: 23 partially edentulous patients were rehabilitated with RPDs at the dental prosthesis clinic at Federal university of Alfenas.  Questionnaires were carried out before and after the rehabilitation treatment, evaluating the level of satisfaction of these patients regarding to the aesthetics and function of chewing food. Masticatory performance (MP) tests were made using a food simulator from condensation silicone Zetaplus – Zermack. Results: After the rehabilitation treatment, the patients reported feeling more satisfied in relation to the aesthetics and function of their teeth. In the statistical analysis, the p-value of the t test found was 0.002, leading to the rejection of the null hypothesis and the conclusion that the geometric mean diameter (GMD) of chewed particles is smaller after the rehabilitation treatment with removable partial dentures. Conclusion: Treatment with RPD provides an improvement in MP and in the level of patient satisfaction with regard to aesthetics and masticatory function, and, it is therefore extremely important for public health as it has a positive impact on improving the quality of life of individuals.